Exploring how live streaming affects immediate buying behavior and continuous watching intention: A multigroup analysis. Issue 1 (2nd January 2022) - Lv, Xingyang; Zhang, Rui; Su, Yiran; Yang, Yang
ABSTRACT: This study employed an attention-interest-desire-action (AIDA) model to explain viewers' immediate purchase decision-making processes and continuous watching intentions within tourism live streaming. Results revealed that informativity, entertainment, and interactivity each positively influenced immersion; immersion positively influenced viewers' interest in tourism products and live streaming. Furthermore, product interest positively influenced buying desire, promoting immediate buying behaviour. Whereas live streaming interest did not influence buying desire. Finally, both product interest and live streaming interest positively impacted continuous watching intention. This study also detected group differences by examining gender, age, watching experience and time pressure.